Dasar Pertimbangan Hakim Dalam Menjatuhkan Pidana Terhadap Pelaku Tindak Pidana Tidak Mematuhi Penyelenggaraan Kekarantinaan Kesehatan Di Masa Pendemi Covid-19 Berdasarkan Keputusan Presiden Nomor 11 Tahun 2020 (Studi Putusan Nomor: 110/Pid.Sus/2021/Pn Sdn) - Suherman, faizal (Hukum dan Masyarakat Madani, 2022)
Health is a need for every human being in living his life. Health is also very important because without good health, every human being will find it difficult to carry out daily activities. "Health is a state of health, both physically, mentally, spiritually and socially that enables everyone to live socially and economically productive lives". The research problem of perpetrators committing criminal acts is not complying with the factors causing health quarantine during the Covid-19 pandemic and the basic considerations in imposing criminal penalties against perpetrators of crimes not complying with policies during the Covid-19 pandemic based on Presidential Decree Number 11 of 2020 on Decision Number: 110/ Pid.Sus/2021/PN Sdn. The research method used in this research is normative juridical. factors that influence perpetrators to commit criminal acts are factors originating from individuals (internal) which are further divided into general internal factors and specific internal factors. While the second factor is a factor that comes from outside the individual (external). Internal factors that are specifically related to psychological conditions (personality problems often cause deviant behavior). Consideration of a reason for the judge in considering the sanctions that will be given to the defendant which is compiled in brief regarding the facts and circumstances along with the evidence obtained from the examination process which is used as the basis for implementing the health implementation as referred to in Article 9 Paragraph (1) and/or hindering the implementation of Health Quarantine so as to cause a Public Health Emergency .
Keywords: Judge's consideration; Criminal act; COVID-19 quarantine.